A Review of Fintech and Waqf Intersections in Academic Debates - Napitupulu, Rodame Monitorir; Sukmana, Raditya (ZISWAF, 2023)
In 2022, Indonesia was ranked 3rd in the utilization of Islamic fintech on a global scale. Despite this accomplishment, waqf institutions continue to face challenges in embracing fintech. Therefore, this research aimed to investigate the extent of fintech-related research on waqf and its implications for the institutions in effectively harnessing fintech in their activities. It adopted a qualitative research approach, relying on Scopus-indexed documents as the primary source of data. Subsequently, the data were analyzed using the Publish or Perish (PoP) tool, following the Systematic Literature Review with PRISMA procedure, and supplemented with content analysis. The results showed noteworthy insights, where Ascarya, A emerged as the most influential author, while Hudaefi, F.A. claimed the highest number of citations. The publication with the greatest influence was the International Publication of Islamic and Middle Eastern Finance and Management, while the most influential affiliations were Universitas Airlangga and Universiti Brunei Darussalam. Indonesia was the most influential country in generating fintech on the waqf subject of the document. Among the 19 relevant papers examined, only 5 (26.32%) focused on the discussion of fintech's impact on waqf. This statistic highlighted the potential for further development of fintech by waqf institutions. Several opportunities for such development emerge, including the creation of waqf applications, the adoption of crowdfunding fintech, the exploration of waqf blockchain, the implementation of WaqfCoin, and the establishment of online platforms for public reporting of waqf fund activities.